Development of a Scale: Self-Efficiency of English Language Teachers for the Education of Gifted Students - ?rem G?RG?N (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
The aim of this study is to develop a scale to measure Self-Efficiency levels of the English Teachers for the Education of gifted students. This research in survey method was carried out with 352 volunteer English Language Teachers (291 women, 61 men) who worked in the 2020-2021 academic year in the Educational Institutions related to the Ministry of National Education in Turkey. To find out validity and reliability of the scale the data set was randomly divided into two. As the result of EFA analysis on the first data set a two-dimensional scale was obtained. The structure obtained was confirmed in the second data set. As a result of discriminant validity test and convergent validity test on both data sets, the scale was found acceptable. After the validity processes, reliability processes were also applied for both separate data sets. For the whole scale, the Cronbach's alpha data coefficient was found as 0.88 in the first data set and it was found 0.87 in the second data set. Results of the analysis revealed that, the Self-Efficiency of the English Teachers for the Education of Gifted Students Scale provides valid and reliable results